2006
DOI: 10.1108/09684880610662042
|View full text |Cite
|
Sign up to set email alerts
|

Workplace stress and the student learning experience

Abstract: Purpose -To investigate the possible effects of workplace stress in academics on the student learning experience. Design/methodology/approach -Questionnaires were designed and distributed to all academic staff at a Scottish Higher Education Institute. This measured perceived levels of stress amongst academic staff and the possible impact of this on the learning experience of students. Findings -Stress can be seen to impact both negatively and positively on the student learning experience. However, over half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 9 publications
7
44
0
9
Order By: Relevance
“…Isso significa que, caso não seja tratado adequadamente, o stress produz resultados negativos, uma vez que a queda no desempenho do discente não só afeta o estudante e a instituição, mas causa um impacto direto sobre a sua experiência de aprendizagem (Stevenson & Harper, 2006).…”
Section: Tabela 1 Resultado Do Ajuste Do Modelo Por Meio Do Critério unclassified
“…Isso significa que, caso não seja tratado adequadamente, o stress produz resultados negativos, uma vez que a queda no desempenho do discente não só afeta o estudante e a instituição, mas causa um impacto direto sobre a sua experiência de aprendizagem (Stevenson & Harper, 2006).…”
Section: Tabela 1 Resultado Do Ajuste Do Modelo Por Meio Do Critério unclassified
“…Ini selaras dengan beberapa sorotan karya seperti yang dibincangkan di dalam bab tiga. Antaranya Stevenson & Harper (2006) dan Tehrani (2002. Pada pandangan mereka, seseorang itu akan mengalami stres sekiranya wujud pengurusan dan pentadbiran serta organisasi yang lemah.…”
Section: Perbincangan Dan Rumusanunclassified
“…Challenging stimulus can lead to positive outcomes such as motivation and improved task performance while distress can result in anxiety, feelings of loneliness, nervousness depression, social dysfunction, sleeplessness and even suicidal intention. This is similar to (Ongori et al, 2009), (Tweed et al, 2004) and (Stevenson and Harper, 2006). In addition, it is important that stress management programs be created to address stress among university students.…”
Section: Introductionmentioning
confidence: 67%
“…In Malaysia, researchers as (Redhwan et al, 2009) mention a handful of studies conducted on stress and coping styles focused on nurses, international students, school athletes, university students, and medical students and among prescience students. With regard to (Richlin-Klonsky et al, 2003) and (Redhwan et al, 2009) as well as (Stevenson and Harper, 2006), (Ratanasiripong et al, 2005) and (Bessie Ong & K C Cheong, 2009), however not much studies have been conducted to understand the identified stressors (Academic, Time/Balance, Interpersonal/Self, Relationship/Social and Family) among university students, Malaysian Universities includes Multimedia University of Malaysia (MMU). Therefore, it would be great to identify which stressors cause the highest types of stress among them.…”
Section: Motivation Of the Studymentioning
confidence: 99%
See 1 more Smart Citation